DETERMINAN FAKTOR NILAI PERUSAHAAN PADA PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTARDI BURSA EFEK INDONESIA 2014-2018 - Dody Salden Chandra (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2019)
The purpose of this study was to determine the effect of Debt to Equity Ratio and Return on Equity on Firm Value either partially or simultaneously. The approach used in this study is an associative approach and the type of data used is quantitative. The population in this study were 11 food and beverage companies listed on the Indonesia Stock Exchange with a sample of 7 companies. The data collection technique used the documentation method, while the data analysis technique used in this study was multiple linear regression analysis. Data management in this study uses SPSS (statistical package for the social sciences) version 22.00. The results of this study indicate that partially Debt to Equity Ratio has a significant effect on Firm Value, Return on Equity has a significant effect on Firm Value and simultaneously Debt to Equity Ratio and Return on Equity have a significant effect on Firm Value